Inverse Relationship between Tumor Proliferation Markers and Connexin Expression in a Malignant Cardiac Tumor Originating from Mesenchymal Stem Cell Engineered Tissue in a Rat in vivo Model - Spath, Cathleen; Schlegel, Franziska; Leontyev, Sergey; Mohr, Friedrich W.; Dhein, Stefan (Frontiers in Pharmacology, 2013)
Background: Recently, we demonstrated the beneficial effects of engineered heart tissues for the treatment of dilated cardiomyopathy in rats. For further development of this technique we started to produce engineered tissue (ET) from mesenchymal stem cells. Interestingly, we observed a malignant tumour invading the heart with an inverse relationship between proliferation markers and connexin-expression. Methods: Commercial CD54+/CD90+/CD34-/CD45- bone marrow derived mesenchymal rat stem cells (cBM-MSC), characterized were used for production of mesenchymal stem-cell-ET (MSC-ET) by suspending them in a collagen-I, matrigel-mixture and cultivating for 14 days with electrical stimulation. 3 MSC-ET were implanted around the beating heart of adult rats for days. Another 3 MSC-ET were produced from freshly isolated rat bone marrow derived stem cells (sBM-MSC). Results: 3 weeks after implantation of the MSC-ETs the hearts were surgically excised. While in 5/6 cases the ET was clearly distinguishable and was found as a ring containing mostly connective tissue around the heart, in 1/6 the heart was completely surrounded by a huge, undifferentiated, pleomorphic tumour originating from the cMSC-ET (cBM-MSC), classified as a high grade malignant sarcoma. Quantitatively we found a clear inverse relationship between cardiac connexin-expression (Cx43, Cx40 or Cx45) and increased Ki-67 expression (Cx43: p<0.0001, Cx45: p<0.03, Cx40: p<0.014). At the tumour-heart border there were significantly more Ki-67 positive cells (p=0.001), and only 2% Cx45 and Ki-67-expressing cells, while the other connexins were nearly completely absent (p<0.0001). Conclusions and hypothesis: These observations strongly suggest the hypothesis, that invasive tumour growth is accompanied by reduction in connexins. This implicates that gap junction communication between tumour and normal tissue is reduced or absent, which could mean that growth and differentiation signals can not be exchanged.